2014
DOI: 10.1593/neo.132076
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Derived Factors Mediate Breast Cancer Cell Migration through CD44 Receptor-Ligand Interactions in a Novel Ex Vivo System for Analysis of Organ-Specific Soluble Proteins

Abstract: Breast cancer preferentially metastasizes to lung, lymph node, liver, bone, and brain. However, it is unclear whether properties of cancer cells, properties of organ microenvironments, or a combination of both is responsible for this observed organ tropism. We hypothesized that breast cancer cells exhibit distinctive migration/growth patterns in organ microenvironments that mirror common clinical sites of breast cancer metastasis and that receptor-ligand interactions between breast cancer cells and soluble org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 46 publications
3
65
0
Order By: Relevance
“…In addition to increased migratory patterns, MDA-MB-231 and MDA-MB-468 cell lines demonstrated cell line specific patterns of proliferation in response to organ-CM. MDA-MB-231 cells showed increased proliferation in the presence of liver and lung-CM and MDA-MB-468 cells showed increased proliferation in the presence of lung-CM [50] . These results indicate the potential of the lung microenvironment for promoting metastatic progression of breast cancer cells.…”
Section: The Soluble Lung Microenvironmentmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to increased migratory patterns, MDA-MB-231 and MDA-MB-468 cell lines demonstrated cell line specific patterns of proliferation in response to organ-CM. MDA-MB-231 cells showed increased proliferation in the presence of liver and lung-CM and MDA-MB-468 cells showed increased proliferation in the presence of lung-CM [50] . These results indicate the potential of the lung microenvironment for promoting metastatic progression of breast cancer cells.…”
Section: The Soluble Lung Microenvironmentmentioning
confidence: 92%
“…Organs representing common sites of breast cancer metastasis (lung, bone, liver, brain, LN) are isolated from healthy mice and used to generate organ-conditioned media (CM). Using this model, Chu et al (2014) demonstrated that different human breast cancer cell lines show specific chemotactic and proliferative behaviours in response to various organ-CM, reflective of their metastatic behaviours in vivo [50] . Specifically, the most aggressive of the cell lines, MDA-MB-231, showed increased migration patterns towards bone, lymph node, and lung-CM.…”
Section: The Soluble Lung Microenvironmentmentioning
confidence: 99%
“…The percentage of viable cells was about 99% and the cell number was about 3×10 4 cells/mL. Cells in exponential growth were placed in 96-well plates at a final concentration of 3×10 4 cells/mL and then treated with differing concentrations of DTIC for differing periods of time. Cell viability was assessed using the Cell Counting Kit (CCK-8) assay (Beyotime Biotechnology, Shanghai, China) according to the manufacturer's instructions.…”
Section: Materials and Methods Cck-8 Assay To Analyze Cell Viabilitymentioning
confidence: 99%
“…[1][2][3][4] Tumor cells with CD44 receptor proteins (CD44 treatment of melanoma. [8][9][10] Increased levels of soluble CD44s (the standard isoform, comprising exons 1-5 and 16-20) and soluble CD44v (splice variants containing variable exons) in the circulation of cancer patients have been considered prognostic markers for disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation